A History of YIVO’s Prewar Archival Collections from 1925 to 2001 - Halpern, Stefanie (Judaica Librarianship, 2022)
This article discusses YIVO's prewar collections, their looting and dispersion during the Holocaust, and the various subsequent efforts to recover them. The article includes a brief overview of YIVO's founding and prewar activities; a discussion of the Nazi looting of YIVO's materials during the Holocaust and the heroic efforts by Jews to save these materials during and after the war; YIVO's shift of its headquarters to New York City in 1939–1940; the US Government restitution of materials to YIVO in 1947; and efforts to reclaim additional materials from Lithuania from 1989 to 2001. The article closes with a brief note on YIVO's newly completed Vilna Collections Project to digitally reunite YIVO's pre-war materials in New York City with materials housed in three Lithuanian repositories.